Foreign students’ intercultural communication competencies at learning Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
In the article the problem of forming of individual’s ability to effective intercultural communication, types of intercultural communication and attributes of successful interaction between representatives of different cultures are examined.
Keywords: competency; intercultural communication; culture; intercultural contacts